Efektivitas Relaksasi Dzikir Sebagai Metode Mengatasi Anxiety Pada Mahasiswa Psikologi UHAMKA - Muhammad Fauzan; Laila Nur Jamilah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Anxiety is a psychological condition characterized by feelings of fear and worry about an uncertain future. Dhikr is a technique whose aim is to get closer to Allah. This research also uses phenomenology and a qualitative approach for its research design, chosen because it allows researchers to gain a deeper understanding from the results of interviews regarding the effectiveness of dhikr relaxation as a method for dealing with anxiety in UHAMKA Psychology Students. In this exploration, testing was carried out using purposive examination with the Miles and Huberman information inquiry data analysis model. Qualitative information is examined interactively and consistently to produce results, resulting in information data saturation. The results obtained in this research are that dhikr relaxation has an effect on overcoming anxiety in UHAMKA Psychology students.